Neuromuscular function following prolonged intense self-paced exercise in hot climatic conditions - Périard, J. D.; Cramer, M. N.; Chapman, P. G.; Caillaud, C.; Thompson, M. W. (European Journal of Applied Physiology, 2011)
Muscle weakness following constant load exercise under heat stress has been associated with hyperthermia-induced central fatigue. However, evidence of central fatigue influencing intense self-paced exercise in the heat is lacking. The purpose of this investigation was to evaluate force production capacity and central nervous system drive in skeletal muscle pre- and post-cycle ergometer exercise in hot and cool conditions. Nine trained male cyclists performed a 20-s maximal voluntary isometric contraction (MVC) prior to (control) and following a 40-km time trial in hot (35°C) and cool (20°C) conditions. MVC force production and voluntary activation of the knee extensors was evaluated via percutaneous tetanic stimulation. In the cool condition, rectal temperature increased to 39.0°C and reached 39.8°C in the heat (P < 0.01). Following exercise in the hot and cool conditions, peak force declined by ~90 and ~99 N, respectively, compared with control (P < 0.01). Mean force decreased by 15% (hot) and 14% (cool) (P < 0.01 vs. control). Voluntary activation during the post-exercise MVC declined to 93.7% (hot) and 93.9% (cool) (P < 0.05 vs. control). The post-exercise decline in voluntary activation represented ~20% of the decrease in mean force production in both conditions. Therefore, the additional increase in rectal temperature did not exacerbate the loss of force production following self-paced exercise in the heat. The impairment in force production indicates that the fatigue exhibited by the quadriceps is mainly of peripheral origin and a consequence of the prolonged contractile activity associated with exercise.